2019
DOI: 10.1071/an18311
|View full text |Cite
|
Sign up to set email alerts
|

Productivity and profitability of alternative steer growth paths resulting from accessing high-quality forage systems in the subtropics of northern Australia: a modelling approach

Abstract: Beef producers have to determine the best allocation of a limited resource of high-quality forage. This analysis assessed the most profitable way of incorporating high-quality forages into the whole-of-life steer growth path on forage systems in central Queensland, using property-level, regionally relevant herd models that determine whole-of-business productivity and profitability over a 30-year investment period. Twenty-two growth paths (liveweight change over time) from weaning to marketing were investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
(12 reference statements)
1
5
0
Order By: Relevance
“…Our findings, both here and in other studies (e.g. Bowen and Chudleigh 2019), are in accord with these authors who also identified that capital constraints and perceived risk were likely to be important factors influencing the adoption of alternative management strategies and technologies by livestock producers across Australia. Diversifying sources of income can have the effect of both smoothing income over time and improving average profitability which, consequently, can reduce risks from climate variability and assist with drought preparedness and resilience (Buxton and Stafford Smith 1996;Freebairn 2019).…”
supporting
confidence: 92%
“…Our findings, both here and in other studies (e.g. Bowen and Chudleigh 2019), are in accord with these authors who also identified that capital constraints and perceived risk were likely to be important factors influencing the adoption of alternative management strategies and technologies by livestock producers across Australia. Diversifying sources of income can have the effect of both smoothing income over time and improving average profitability which, consequently, can reduce risks from climate variability and assist with drought preparedness and resilience (Buxton and Stafford Smith 1996;Freebairn 2019).…”
supporting
confidence: 92%
“…Leucaena leucocephala is a tropical leguminous tree that is planted in rows with improved grass species for beef cattle fodder. In central Queensland, leucaena-grass pastures substantially increase beef production and profitability compared with perennial grass pastures as they support higher stocking rates, longer grazing periods, and higher daily cattle liveweight gain due to increased diet quality (Bowen et al 2018). However, there is little data documenting diet selection of cattle grazing leucaena-grass pastures over different seasonal conditions with varying forage availability.…”
Section: Referencesmentioning
confidence: 99%
“…Leucaena leucocephala is a legume fodder crop that grows in tropical and subtropical environments. Leucaena provides a high quality feed for cattle boosting liveweight gain both per animal and per hectare, improving profitability for steer turnover by 121% compared with the base scenario of grazing buffel grass (Bowen and Chudleigh 2018). A number of commercial leucaena cultivars, Cunningham, Peru, Taramba, El Salvadore, and Wondergraze, are used in Queensland.…”
Section: Enriching For Rumen Bacteria To Degrade Thementioning
confidence: 99%
“…This system has the potential to fill the winter feed gap to maintain high weight gains for close to 12 months of the year, compared with only 7-9 months without winter forages. While field research into the productive capacity and resulting economic outcomes of such systems needs to be undertaken, economic analysis of a system, involving grazing cattle on oats in the winter months and leucaena-grass pasture for the remainder of the year in central Queensland (Bowen and Chudleigh 2018b), indicates costs of establishing and managing the winter forage could out-weigh the increased weight gains and additional income potential from marketing heavy cattle earlier. Without irrigation, such a system may have production merits only in higher rainfall years.…”
Section: Filling Feed Gaps With Winter Foragesmentioning
confidence: 99%
“…The long-term economic benefits of perennial pasture grazing systems with leucaena are also substantial, even when the high cost of establishment is included. Gross margins per hectare can be doubled (Bowen et al 2018) compared with grass-only pastures, and whole-farm profitability (annualized net present value) for a breeding and finishing enterprise containing around 1,500 adult equivalents (AE = 450 kg dry animal at maintenance) can be improved by more than $40,000/annum for 30 years when compared with the same grazing business without leucaena (Bowen and Chudleigh 2018a;2018b).…”
Section: Introductionmentioning
confidence: 99%